4‑Hydroxyproline-Derived Sustainable Polythioesters: Controlled Ring-Opening Polymerization, Complete Recyclability, and Facile Functionalization - Yuan, Jingsong; Xiong, Wei; Zhou, Xuhao; Zhang, Yi; Shi, Dong; Li, Zichen; Lu, Hua (Journal of the American Chemical Society, 2019)
The sustainable production of chemically recyclable polymers presents a significant opportunity to polymer scientists to tackle the growing environmental and energy problems of current petroleum-based plastics. Despite recent advances, however, there are still pressing needs for an expanded horizon of chemically recyclable polymers. Herein, we introduce a new paradigm of biosourced polythioesters (PTEs) with high polymerizability and complete recyclability under mild and economical conditions. The thiolactone monomers with a high ring strain can be easily prepared in a two-step process from 4-hydroxyproline. Controlled ring-opening polymerizations (ROP) using inexpensive and weak bases afford PTEs with high molar masses (M n) up to 259 kg mol–1 and narrow dispersities generally below 1.15. The properties of PTEs can be readily adjusted by copolymerization and/or pre/post-functionalization on the side chains. Selective and complete depolymerizations of the PTEs in dilute solution at ambient to modest temperatures recycle clean monomers. Density functional theory (DFT) calculation of model reactions provides mechanistic insights and highlights the importance of judicious molecular design. Taken together, the unique ROP/depolymerization chemistry of such PTEs may offer a sustainable solution for creating and manufacturing high-value materials such as optical/photochemical plastics, self-immolative polymers, and degradable biomaterials under situations where recycle and reuse are indispensable.